3+3(2y-8)-3(4y+4)-10=

Simple and best practice solution for 3+3(2y-8)-3(4y+4)-10= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+3(2y-8)-3(4y+4)-10= equation:


Simplifying
3 + 3(2y + -8) + -3(4y + 4) + -10 = 0

Reorder the terms:
3 + 3(-8 + 2y) + -3(4y + 4) + -10 = 0
3 + (-8 * 3 + 2y * 3) + -3(4y + 4) + -10 = 0
3 + (-24 + 6y) + -3(4y + 4) + -10 = 0

Reorder the terms:
3 + -24 + 6y + -3(4 + 4y) + -10 = 0
3 + -24 + 6y + (4 * -3 + 4y * -3) + -10 = 0
3 + -24 + 6y + (-12 + -12y) + -10 = 0

Reorder the terms:
3 + -24 + -12 + -10 + 6y + -12y = 0

Combine like terms: 3 + -24 = -21
-21 + -12 + -10 + 6y + -12y = 0

Combine like terms: -21 + -12 = -33
-33 + -10 + 6y + -12y = 0

Combine like terms: -33 + -10 = -43
-43 + 6y + -12y = 0

Combine like terms: 6y + -12y = -6y
-43 + -6y = 0

Solving
-43 + -6y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '43' to each side of the equation.
-43 + 43 + -6y = 0 + 43

Combine like terms: -43 + 43 = 0
0 + -6y = 0 + 43
-6y = 0 + 43

Combine like terms: 0 + 43 = 43
-6y = 43

Divide each side by '-6'.
y = -7.166666667

Simplifying
y = -7.166666667

See similar equations:

| 4w-26=38 | | 10x-4y=k | | 6a=14a | | -4x-36=34-6x | | 8(x+6)=8x+32 | | 3a+4b-3+4a=7 | | 8x+36=12x-20 | | 4x+40=16 | | 3x+4y=3-2 | | 6(x-12)+5(x-13)=6 | | X+.6x=265 | | V=(a+4)(a-5)(2a) | | P=80-20q | | X-11=32 | | 4tanx+3=7 | | 9-2x=y | | 0.01x^2+0.03x-0.10=0 | | 6/14/tan | | 7(x-8)-8x-7=x+7-x-2 | | tanx=6/14 | | 17b=w | | 5x^3=40x^2-80x | | 2x+3=12x-76 | | -5x^3-40x^2-80x=0 | | 2x+3=412x-76 | | a^2-4ab+4b^2-81=0 | | 6(3x+1)-10x=22 | | 2x(3x+6)=2x+17 | | 64=8*a^3 | | (4-y)(4-y)+y^2=16 | | 5/6=2/0.6 | | 9x+-5y=3 |

Equations solver categories